Reducing medical cannabis use risk among Veterans: A descriptive study - Laura M. Harris-Lane; Mitchell Sheehy; Courtney A. Loveless; Joshua A. Rash; David P. Storey; Gregory K. Tippin; Vikas Parihar; Nick Harris (Harm Reduction Journal)
Abstract Background Canadian Veterans experiencing chronic pain report concerns about accessing accurate information on the risks associated with medical cannabis (MC) use. The Lower Risk Cannabis Use Guidelines (LRCUG) were developed to equip individuals who use cannabis recreationally with safer-use strategies. Many of the harm reduction recommendations for recreational cannabis use are relevant and important considerations for MC use. The primary objective of our study was to assess Canadian Veterans’ awareness of and interest in the LRCUG, and engagement in potential higher-risk MC use behaviours. Methods Canadian Armed Forces Veterans living with chronic pain (N = 582) were recruited online and through the Chronic Pain Centre of Excellence for Canadian Veterans. Participants completed measures on: cannabis use (never, past, current use), sources of cannabis knowledge, mental health, and awareness of and interest in receiving the LRCUG. Chi-Square and post-hoc analyses characterized the sample and assessed for demographic differences based on cannabis use status and awareness of the LRCUG. Engagement in higher-risk MC use behaviours were aligned to LRCUG recommendations, and detailed descriptively. Results Veterans who currently use cannabis were more likely to be unemployed (z = 3.62, p < .01), released as a Non-Commissioned Officer (z = -3.83, p < .01), and unable to work due a disability (z = -3.43, p < .01) than Veterans who do not currently use. Less than 30% of Veterans were aware of the LRCUG, with greater awareness among individuals who currently use cannabis (n = 356). Engagement in higher-risk MC use behaviours that contradicted LRCUG recommendations ranged from ~ 9% to ~ 85%. Approximately 9% of Veterans experienced co-morbid mental health concerns, yet their MC use was not for mental health purposes (LRCUG recommendation #7). Additionally, almost 85% of Veterans engaged in daily MC use (LRCUG recommendation #5). The majority of Veterans who currently use cannabis engaged in two or more higher-risk MC use behaviours (60.2%; LRCUG recommendation #12). Almost half of all Veterans received their cannabis information from a healthcare provider or the internet. Conclusions Our study suggests the importance of safer use guidelines tailored for MC use. Development of lower-risk MC use guidelines can support prescribing practitioners and Veterans with information needed for safer and better-informed MC use decisions, tailored to patients’ needs and circumstances.